In vitro evaluation of the insecticide and larvicide effects of eight essential oils on mealworm (Alphitobius diaperinus) Avaliação In Vitro Dos Efeitos Inseticida E Larvicida De Oito óleos Essênciais Sobre O Cascudinho Aviário (Alphitobius diaperinus) - Volpato A.* (2018)
© 2018, Universidade Federal do Parana.Alphitobius diaperinus, the aviary mealworm, is an insect that stands out in poultry to be vector of pathogens and difficult to control. The difficulty in control is related to the contraindication in the use of chemicals while the birds are in the aviary, and large losses can occur as a result of high infestations. Therefore, natural products with potential insecticide and larvicide could be used without harming the birds, as well as without leaving residue in chicken meat. As a result, this study aimed to verify the effect of Lemon Grass oil (Cymbopogon citratus), Cedar (Cedrus atlantica), Ginger (Zingiber officinale), Geranium (Pelargonium graveolens), Junipero (Juniperus communis), Palmarosa (Cymbopogon martinii), Thyme (Thymus vulgaris) and Vetiver (Vetiveria zizanioides) on the susceptibility of A. diaperinus. The tests were performed in triplicate with essential oils at concentrations of 1, 5, and 10%. In order to validate the tests two controls were used: untreated and diluent (Triton). The larvicide and insecticidal effects of lemon grass oil was not satisfactory because the mortality rate higher than 50% was reached only 14 and 16 days after start of the test, respectively. Cedar oil did not show significant effect on adults and larvae, as the mortality values were less than 50% at all concentrations tested. The effect of insecticide and larvacide were not observed in the other oils at concentrations tested in this experiment (P > 0.05). Therefore, based on the results of the in vitro insecticidal and larvicidal low-action tests of the oils tested on A. diaperinus, we conclude that they are inadequate for the alternative control of this pest.